SERUM POST PRANDIAL GLUCOSE LEVEL LESS THAN FASTING GLUCOSE!? - SREEKANTHA (International Journal of Pharma and Bio Sciences, 2012)
Blood glucose estimation is the most common investigation in the medical practice in all disciplines. Altered values of blood glucose are very common in laboratory but here we are reporting the fasting blood glucose (FBG) more than the post prandial blood glucose(PPBG).This type of results are confusing for the consultants to make relevant diagnosis and treatment. Blood glucose estimation was done using Glucose oxidase method and tabulated the reports of 24 subjects with FBG more than PPBG in the period of 3 months along with estimation of Glyco-Hb for mean comparison in semi auto analyzer A-15.Here we are trying to explain the various factors which may contribute to the development of FBG more than the PPBG, methodology of evaluation of these subjects.